1998
DOI: 10.1073/pnas.95.7.4055
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of neurosecretory cells releasing pheromonotropic neuropeptides in the moth Bombyx mori

Abstract: Short-and long-term firing patterns of neurosecretory cells releasing pheromonotropic neuropeptides in the silkworm moth Bombyx mori were examined. The cells showed three types of rhythmic changes in firing activity. Bursting activities with an interval of several seconds were synchronized with rhythmic abdominal motions for calling behavior. A slow f luctuation in firing activity over a period of several minutes depended on cyclic alternations of the f low of hemolymph. The electrical activity displayed a die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Alternatively, the restrainable stimulus of the abdomen could be sensed by mechanical receptors scattered over the abdominal wall and muscles. Recently, it was shown that mating with a pr-male or a tactile stimulation of abdominal tip inhibits the activity of neurosecretory cells releasing PBAN (Ichikawa, 1998), which supports our results. All values do not differ statistically.…”
Section: Discussionsupporting
confidence: 93%
“…Alternatively, the restrainable stimulus of the abdomen could be sensed by mechanical receptors scattered over the abdominal wall and muscles. Recently, it was shown that mating with a pr-male or a tactile stimulation of abdominal tip inhibits the activity of neurosecretory cells releasing PBAN (Ichikawa, 1998), which supports our results. All values do not differ statistically.…”
Section: Discussionsupporting
confidence: 93%
“…mori female pheromone release also shows a circadian rhythm: the release of pheromone increases at the beginning of photophase to reach a peak 6·h later; this peak lasts for 2·h before decreasing until the beginning of scotophase (Ichikawa, 1998). The circadian variation of the male's sensitivity to pheromone allows the male to locate more efficiently the female during its pheromone release peak window.…”
Section: Circadian Variation Of Serotonin and Of Bombykol Sensitivitymentioning
confidence: 99%
“…2 and 4), thereby indicating that sex pheromone production is under the control of a circadian pacemaker. It is often difficult to find a robust circadian rhythm in pheromone production by measuring pheromone contents in the gland because of a slow decline of pheromone titers after a stop of PBAN secretion (decapitation or mating) (Ichikawa, 1995(Ichikawa, , 1998. It should be noted that the proportion of females expressing a circadian oscillation of PBAN cells in DD was significantly low (10%); one reason being that complete darkness may be repelled by many female moths of Bombyx mori to perform calling behavior, because an abrupt termination of illumination of 100 lx at a mid-photophase stopped firings of PBAN cells and such a silent state often continued for as long as the darkness continued (unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term chronic recordings from the maxillary nerve branch revealed complex firing activity rhythms of PBAN producing cells that are closely related to calling behavior, circulation of haemolymph, and diurnal changes in pheromone titers in a light/dark cycle (Ichikawa, 1998). Because electrical signals from neurosecretory cells can be sampled from a single female moth with a higher temporal resolution, analyses of the diurnal firing rhythms of PBAN cells may facilitate understanding of circadian control of pheromone production of individual moths and the nature of a circadian oscillator of the adult silkmoth.…”
Section: Introductionmentioning
confidence: 99%